Tourism as a Cultural Ecosystem Service in Protected Areas: A Review of Emerging Issues - Catherine KIFWORO; Kaitano DUBE (African Journal of Hospitality, Tourism and Leisure)
Tourism as a cultural ecosystem service within protected areas remains an under-researched domain despite its pivotal role in supporting conservation and host communities around these entities. This study used a bibliometric approach to review 116 articles from the Scopus database related to tourism and cultural ecosystem services in protected areas. Citation, bibliographic coupling, co-authorship, and co-occurrence analyses were conducted using VOS Viewer. The findings showed few studies from the Global South, particularly in African countries. The extant studies leaned towards ecology rather than tourism perspectives. The dominant themes were assessments, mapping, supply and demand, land use planning, conservation, use of social media research, human-nature interactions, climate change impacts and sustainable development. The evident gaps for further studies in tourism were niche tourism products, climate change adaptability and mitigation, impacts of tourism, stakeholder engagement and management, payment for ecosystem services, using social indicators for assessments and efficacy of using social media for tourism research. Empirical studies would be particularly key in providing primary data to inform policy and practice. The study points out knowledge gaps and sets the agenda for future studies.